2001
DOI: 10.1046/j.1528-1157.2001.042007930.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Men Taking Carbamazepine, Oxcarbazepine, or Valproate for Epilepsy

Abstract: Summary:Purpose: Antiepileptic drugs (AEDs) may affect serum thyroid hormone concentrations. This study aimed to evaluate thyroid function in men taking carbamazepine (CBZ), oxcarbazepine (OCBZ), or valproate (VPA) for epilepsy.Methods: Ninety men with epilepsy (40 taking CBZ, 29 taking OCBZ, and 21 taking VPA monotherapy) and 25 control subjects participated in the study. After clinical examination, a blood sample for hormone, ␥-glutamyl-transferase (GGT) and antibody (ab) assays was obtained.Results: Serum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
86
2
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 32 publications
(47 reference statements)
14
86
2
5
Order By: Relevance
“…These data are in agreement with previous papers that found normal thyroid hormone levels (19,20,25,(28)(29)(30). By contrast, other studies (11,31) found normal thyroid hormone levels while TSH levels were increased.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data are in agreement with previous papers that found normal thyroid hormone levels (19,20,25,(28)(29)(30). By contrast, other studies (11,31) found normal thyroid hormone levels while TSH levels were increased.…”
Section: Discussionsupporting
confidence: 93%
“…The clinical significance of this increase is uncertain but seems to be a compensatory response in at least some of the patients. No association was also found between serum thyroid hormone concentrations and VPA related obesity (30,33).…”
Section: Discussionmentioning
confidence: 84%
“…Various AEDs, either carbamazepine, or phenytoin, or sodium valproate and additional diazepam or clonazepam were used to treat seizures in the acute phase. In a study of thyroid function in patients who were taking carbamazepine and oxcarbamazepine showed that carbamazepine can lower serum thyroid hormones [23]. Antiepileptic drugs may be useful and justified during the initial treatment of seizures till you reach the diagnostic confirmation and then antithyroid drug alone will be helpful to prevent seizure recurrences except in proved SSS thrombosis where AED may be continued in view of hemorrhagic and thrombotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation with thyrotropin releasing hormone (TRH) has given discrepant results (Franklyn, 1997;Hartoft-Nielsen et al, 2004;Lania et al, 2008). The possible confounding by certain antiepileptic drugs is well-described (Cansu et al, 2006;Isojarvi et al, 2001), inducing a biochemical picture mimicking that of secondary hypothyroidism with decreased peripheral thyroid hormone concentrations and a normal TSH.…”
Section: Tsh Deficiencymentioning
confidence: 99%